Penggunaan Aplikasi Physics Tool dan Software Logger Pro sebagai Alat Pendukung Praktikum Fisika di Sekolah Menengah: Penentuan Konstanta Pegas - Erawati, Wiwi; Ishafit, Ishafi (Universitas Halu Oleo, 2021)
This research aims to determine the spring constant statically using logger pro dan aplikasi physics tool. The method that is used in this research is experimentally by hanging the ballast load as measured the accretion of the spring length using a ruler and measured the initial spring length, then the spring is given the deviation as big as the difference of the spring length accretion with the initial spring length for each mass so that the harmonious vibrations occur for variation of spring load mass (by recording the research video experimentally, afterwards the video is imported into logger pro software). Then do the tracking of spring load motion in the video to obtain the time when the spring is oscillating and the data from Physics Tool Application is imported into Ms. Excel 2007, so the data of time was obtained). the data of oscillation time as the result of logger pro tracking and physics tool application was made into a graph of the relationship of squared period towards load mass variation of (6,354 ± 0,158) Nm-1 with 2,49% relative errors and 97,51% precision from Logger Pro Software and a spring constant with load mass variation of (6,208 ± 0,162) Nm-1 with 2,60% relative errors and 97,40% precision from application physics tool application